Solvent‐Induced Self‐Assembly of Naphthalenediimide Conjugated to Tetraphenylethene through D‐ and L‐Alanine. Issue 9 (4th March 2019) - Goskulwad, Santosh P.; More, Vishal G.; Kobaisi, Mohammad Al; Bhosale, Rajesh S.; La, Dung Duc; Antolasic, Frank; Bhosale, Sidhanath V.; Bhosale, Sheshanath V.
Abstract: Herein, the synthesis and supramolecular self‐assembly of naphthalenediimide (NDI)‐tetraphenylethene (TPE) conjugates with l‐alanine (coded as: 1 ) and d‐alanine (coded as: 2 ) was investigated. The pair stereoisomer molecules were designed to undergo self‐assembly under solvophobic effects. Mixtures of THF–water was used to fine tune the solvophobic effect leading to microbelt for both 1 and 2 in 40% v/v of THF in H2 O, while microbelt and particulate microsphere supramolecular structures were observed in 20%, v/v THF in H2 O. When 10% THF in H2 O was employed derivative 1 produces belt‐like structures, however, 2 produces microsphere. Less uniformly defined microstructure morphologies of 1 and 2 were formed in THF/hexane and DCM/hexane. The solvophobic effect on self‐assembly further evidenced using UV/Vis, fluorescence, circular dichroism, X‐ray diffraction (XRD) spectroscopies. DLS used to evaluate formation of assembly in solution, DFT (density functional theory) and TD‐DFT (time dependent density functional theory) molecular modelling support the hypothesis. Scanning electron microscopy used to visualise formation of supramolecular self‐assembled nano‐ and micro‐structures. Abstract : Supramolecular self‐assembly behaviour of naphthalenediimide (NDI)‐ tetraphenylethene (TPE) conjugates with l‐ (1 ) and d‐alanine spacer (2 ) was investigated. The molecules were designed to undergo self‐assembly under solvophobic effects leading to various structures such as microbelt, fibrils, microsphere etc. depending on solvent proportion of THF/H2 O, THF/hexane and DCM/hexane. Even NDI bearing TPE moieties showing ACQ effect rather than AIE due to photoinduced charge transfer between TPE donor and NDI acceptor.